An esterase from Penicillium decumbens P6 involved in lignite depolymerization. (15th February 2018) - Yang, Yi; Yang, Jinshui; Li, Baozhen; Wang, Entao; Yuan, Hongli
Highlights: An esterase capable of lignite depolymerization was purified from Penicillium decumbens . The contribution of the esterase to the lignite depolymerization was about 40%. This is the first report to verify lignite depolymerization of isolated esterase in vitro . The depolymerization product (bHA) can significantly promote the growth of asparagus lettuce. Abstract: In this study, lignite was degraded using a purified esterase from Penicillium decumbens P6 for the first time. The esterase was purified using ammonium sulfate precipitation, anion exchange and gel filtration chromatography. The recovery and purification yield of the enzyme were 15% and 83 folds, respectively. The molecular weight of the purified enzyme was about 45 kDa. Both crude and purified esterases were studied for lignite depolymerization. The tendency of depolymerization by crude enzyme was consistent with the enzyme secreted in the medium. Along with the increased purified esterase concentration from 8 to 50 mg/ml, A450 value increased from 0.38 to 2.08. The contribution of esterase to the depolymerization was about 40% in the crude supernatant. Compared with aHA (crude lignite humic acid), bHA (esterase degraded lignite humic acid) has a lower percentage of aromatic carbon and ester groups, but a higher percentage of aliphatic carbon. bHA can promote the growth of asparagus lettuce. The results demonstrated that lignite was depolymerized by the purified esterase and evidenced the potential of esterase application in conversion of lignite into compounds with high bioactivities.